Performance of petunia crop in response to inoculation with Azospirillum brasilense = Desempeño del cultivo de petunia en respuesta a la inoculación con Azospirillum brasilense - Toffoli, Lucia Mercedes; Medrano, Norma Nelly; Martinez Zamora, Martin Gustavo; Guerrero Molina, María Fernanda; Pedraza, Raúl Osvaldo; Salazar, Sergio Miguel (Facultad de Agronomía y Zootecnia, Universidad Nacional de Tucumán, 2019)
The present study was carried out to analyze the performance of Petunia hybrida when inoculated with Azospirillum brasilense REC3. Parameters evaluated were root length, dry weight of roots and shoots, leaf area, leaf greenness, precocity (days to flowering) and number of flowers in plants. Azospirillum inoculation increased root growth, shoot weight and number of flowers compared to controls. Time to flowering, a fundamental feature from the economic point of view, was shortened in inoculated plants. These findings indicated that inoculation with A. brasilense strain REC3 resulted in an increase in vegetative growth and an early and profuse flowering, thus reducing fertilization costs and environmental pollution.